2008
DOI: 10.1111/j.1469-1795.2008.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate of daytime den sites in a tropical possum: implications for the conservation of tropical arboreal marsupials

Abstract: Tree cavities are an important shelter site for a variety of vertebrate species, including birds, reptiles and mammals. Studies indicate that in most taxa favoured tree hollows are those in larger trees and higher from the ground, generally thought to be related to decreased predation risk and a more optimal thermal environment. However, neither of these ideas has been tested definitively. Here, we investigate the microclimate of daytime den sites in tree hollows of common brushtail possums in tropical norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 31 publications
3
39
1
Order By: Relevance
“…The sampling duration of many studies has often been short, for example only one night (Paclík and Weidinger, 2007), several weeks (Ardia et al, 2006;Isaac et al, 2008), or a few months (Suggitt et al, 2011). In many instances, it is important to know whether the decoupling of microclimate is a consequence of divergence of temperature minima, maxima or both as this may have different implications for different taxa (i.e., in instances where the primary challenge is to avoid very low temperatures, namely 'critical thermal minima', or very high temperatures, namely 'critical thermal maxima').…”
Section: Introductionmentioning
confidence: 99%
“…The sampling duration of many studies has often been short, for example only one night (Paclík and Weidinger, 2007), several weeks (Ardia et al, 2006;Isaac et al, 2008), or a few months (Suggitt et al, 2011). In many instances, it is important to know whether the decoupling of microclimate is a consequence of divergence of temperature minima, maxima or both as this may have different implications for different taxa (i.e., in instances where the primary challenge is to avoid very low temperatures, namely 'critical thermal minima', or very high temperatures, namely 'critical thermal maxima').…”
Section: Introductionmentioning
confidence: 99%
“…In general, endothermic animals using thermally unsuitable nest boxes may experience non-lethal short-term consequences such as reduced growth and body condition, but may also potentially experience high mortality rates during extremely hot or cold weather events [40,52,63]. For example, during cold weather, tree swallow (Tachycineta bicolor (Vieillot, 1808)) chicks in cooler nest boxes were shown to have lower survival, slower growth rates, and smaller body size than those in warmer boxes [41].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rowland et al [40] showed that the eco-physiological costs of thermoregulation are likely to be considerably higher for arboreal marsupials (adult weight range = 1100-4500 g) in nest boxes compared to tree hollows during summer, but marginally lower during winter. There is also some evidence that free-ranging arboreal marsupials avoid nest boxes that experience temperature extremes during hot weather, presumably to avoid heat-stress [63,65].…”
Section: Introductionmentioning
confidence: 99%
“…Ardia et al 2006;Velky et al 2010). It is well documented that tree holes can buffer against temperature fluctuations (Schmid 1998;Sedgeley 2001;Willis & Brigham 2007;Isaac et al 2008) and the change in sleeping site usage that we observed may thus indicate the lower thermoregulatory constraints experienced by the females during the wet season. During the dry season, the lower minimum temperatures, greater temperature fluctuations and low food availability mean that females must expend more energy to maintain a high body temperature.…”
Section: Thermoregulatory Demands and Sleeping Sitesmentioning
confidence: 60%
“…It has been suggested for cavity-nesting birds and bats that the risk of predation decreases with increasing entrance heights (Sedgeley 2001;Fisher & Wiebe 2006). Similarly, there is evidence that tree holes experience lower temperatures when located at greater entrance heights (Isaac et al 2008) and thus allow for larger energy savings as the animals can remain heterothermic for longer periods. It is thus surprising that sleeping sites in tree holes have substantially lower entrance heights than either nests or open sites.…”
Section: Sleeping Site Characteristics and Selection Pressurementioning
confidence: 99%